A real-world pharmacovigilance study of FDA adverse event reporting system (FAERS) events for sunitinib - Zhang, Xusheng; Ren, Xiuli; Zhu, Tianyu; Zheng, Wanjin; Shen, Chengwu; Lu, Cuicui (Frontiers in Pharmacology, 2024)
Background: Sunitinib is approved for the treatment of metastatic renal cell carcinoma (mRCC), imatinib-resistant gastrointestinal stromal tumors (GIST), and advanced pancreatic neuroendocrine tumors (PNET). This study aims to investigate the safety profiles of sunitinib through data mining of the US Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: The individual case safety reports (ICSRs) on sunitinib from 2006 Q1 to 2024 Q1 were collected from the ASCII data packages in the Food and Drug Administration Adverse Event Reporting System (FAERS). After standardizing the data, a variety of disproportionality analyses, including the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the bayesian confidence propagation neural network (BCPNN), and the multi-item gamma poisson shrinker (MGPS) were employed to identify the potential safety signals of sunitinib-associated AEs. Results: A total of 35,923 ICSRs of sunitinib as the “primary suspected” drug were identified within the reporting period. The search detected 276 disproportionate preferred terms (PTs). The most common AEs, including diarrhea, asthenia, decreased appetite, hypertension, and dysgeusia, were consistent with the drug label and clinical trials. Unexpected significant AEs, such as uveal melanocytic proliferation, salivary gland fistula, yellow skin, eyelash discoloration, scrotal inflammation, were detected. The median onset time of sunitinib-related AEs was 57 days (interquartile range [IQR]16-170 days), with most of the ICSRs developing within the first month (n= 4582, 39.73%) after sunitinib therapy as initiated. Conclusion: The results of our study were consistent with routine clinical observations, and some unexpected AEs signals were also identified for sunitinib, providing valuable evidence for the safe use of sunitinib in the real-world and contributing to the clinical monitoring and risk identification of sunitinib.